Fabrication of paper-based microfluidic device. - Kang, Yuli. (2013)
The microfluidic devices based on paper can be served as a new platform applying on various areas including clinical diagnosis, food quality control and environmental monitoring due to its advantages of low-cost, easy to carry and disposable analytical devices.